2012
DOI: 10.1177/0886260512441078
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Women in Video Games

Abstract: Current research suggests a link between negative attitudes toward women and violence against women, and it also suggests that media may condition such negative attitudes. When considering the tremendous and continued growth of video game sales, and the resulting proliferation of sexual objectification and violence against women in some video games, it is lamentable that there is a dearth of research exploring the effect of such imagery on attitudes toward women. This study is the first study to use actual vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…Perhaps the most interesting evidence comes from longitudinal studies, which examine whether playing VVGs at a time one can predict later aggression or violence. Particularly when time one outcomes are controlled, as well as other factors, such as family environment, mental health, gender, and personality, longitudinal evidence overwhelmingly suggests that VVG influences on youths' long-term well-being are minimal (Breuer et al 2015b, Etchells et al 2016, Ferguson 2011, Shibuya et al 2008, Wallenius & Punamäki 2008, Willoughby et al 2012).…”
Section: Research Evidencementioning
confidence: 99%
“…Perhaps the most interesting evidence comes from longitudinal studies, which examine whether playing VVGs at a time one can predict later aggression or violence. Particularly when time one outcomes are controlled, as well as other factors, such as family environment, mental health, gender, and personality, longitudinal evidence overwhelmingly suggests that VVG influences on youths' long-term well-being are minimal (Breuer et al 2015b, Etchells et al 2016, Ferguson 2011, Shibuya et al 2008, Wallenius & Punamäki 2008, Willoughby et al 2012).…”
Section: Research Evidencementioning
confidence: 99%
“…In addition to the theorized link with self-objectification, differences in perception of victims may be influenced by individual factors such as the extent to which a given women endorses rape myths. It has been suggested that a major logical inference of rape myth acceptance is less sympathy for victims [ 27 ], and given that most rape victims will turn to a friend, often a female friend, for support, there are clear negative implications for the impact of rape myth acceptance by women on the likelihood that support will be given when needed. The employment of rape myths indeed has been shown to play a role in how women define and interpret scenarios that meet the legal definition of rape, but which include elements of myths and do not fall into the socially proscribed ideas found in the common rape script [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…(p. 3026) Beck et al 2012 "…the increasingly realistic sexually aggressive violence found in today's video games can influence men's attitudes toward women." (p. 3027) Beck et al 2012 "…women who spend time in virtual environments and playing video games featuring sexualized characters may subsequently self-objectify, and that this self-objectification may in turn lead to generalized negative attitudes toward women in the form of endorsing rape myths."…”
Section: Dill 2007mentioning
confidence: 99%
“…(p. 3026) Beck et al 2012 "…the increasingly realistic sexually aggressive violence found in today's video games can influence men's attitudes toward women." (p. 3027) Beck et al 2012 "…women who spend time in virtual environments and playing video games featuring sexualized characters may subsequently self-objectify, and that this self-objectification may in turn lead to generalized negative attitudes toward women in the form of endorsing rape myths." (p. 359) Fox et al 2014 "It is impossible to ignore the role that media and computer technology play in shaping offender motivation, modus operandi, and in neutralizing guilt and providing justification for offenders' actions."…”
Section: Dill 2007mentioning
confidence: 99%